A novel PLI suppression method in ECG by notch filtering with a modulation-based detection and frequency estimation scheme. (September 2020) - Chen, Yi-Sheng; Lin, Po-Yen; Lin, Yue-Der
Highlights: An algorithm is presented for PLI suppression by notch filtering with a modulation-based detection and frequency estimation scheme. The proposed structure consists of a PLI detector with a frequency estimation mechanism and a tunable notch filter. The proposed approach has been verified by artificially generated sinusoid and practical PLI for ECG signals. The experimental results indicate that the proposed algorithm is reliable. The proposed method can be a promising technique for remote health care or home care applications. Abstract: In this paper, a new algorithm composed of detection, estimation, and filtering has been implemented to suppress power-line interference (PLI) in the contaminated electrocardiogram (ECG) signal. In the proposed system, the detector can transform the measured signal into a complex signal, whose absolute value is compared with a threshold to decide whether PLI is present or not. If PLI is detected, then the estimate of its frequency computed from the estimator is sent to tune a coefficient of the notch filter for precise suppression of PLI without the requirement of any reference input. The proposed approach has been verified by artificially generated sinusoids and practical PLI for ECG signals. The experimental results have shown the efficacy of the proposed method.